JURIDICAL STUDY ON THE TRANSFORMATION OF PT. ASKES (PERSERO) INTO THE SOCIAL INSURANCE MANAGEMENT AGENCY ON HEALTH - Widya Hartati (Fakultas Hukum Universitas Mataram, 2015)
Social insurance management is a state responsibility as mandated in the 1945 Constitution (UUD 45). With the law of BPJS being issued as the managing and executing agency of National Social Security System (SJSN), PT ASKES Persero has been transformed into The Social Insurance Management Agency on Health (BPJS Kesehatan). The findings show that at the early stage after transformation and the BPJS Kesehatan began to operate, the programs managed by PT. ASKES (Persero) were transferred as the programs of BPJS Kesehatan through National Health Insurance Program (JKN). This transformation will cause the changing in the status of PT. Askes (Persero) from being Persero State-Owned Company (BUMN) into a public legal agency that directly reports to The President of Indonesia. The characteristics of BPJS Kesehatan are different from other BUMNs that seek profits. This agency works primarily on community service. The insurance money collected from the insured participants is managed at its best for the participants’ sake. Although this transformation was well prepared and implemented as the planned mechanism, at the practical level this program still has several issues related to the transformation i.e. lack of socialization and promotion, lack of service facility, inaccurate data, and the lack of health personnel. Keywords: Transformation, BPJS Kesehatan, PT. Askes (Persero)